The effects of grape seed extract supplementation on cardiovascular risk factors, liver enzymes and hepatic steatosis in patients with non-alcoholic fatty liver disease: a randomised, double-blind, placebo-controlled study - Parisa Ghanbari; Davoud Raiesi; Roghayeh Alboebadi; Ahmad Zarejavid; Mostafa Dianati; Hamidreza Razmi; Hadi Bazyar (BMC, 2024)
Abstract Background Despite the high antioxidant potential of grape seed extract (GSE), very limited studies have investigated its effect on non-alcoholic fatty liver disease (NAFLD). Therefore, this study was conducted with the aim of investigating the effect of GSE on metabolic factors, blood pressure and steatosis severity in patients with NAFLD. Methods In this double-blind randomized clinical trial study, 50 NAFLD patients were divided into two groups of 25 participants who were treated with 520 mg/day of GSE or the placebo group for 2 months. The parameters of glycemic, lipid profile, blood pressure and steatohepatitis were measured before and after the intervention. Results The GSE group had an average age of 43.52 ± 8.12 years with 15 women and 10 men, while the placebo group had an average age of 44.88 ± 10.14 years with 11 women and 14 men. After 2 months of intervention with GSE, it was observed that insulin, HOMA-IR, TC, TG, LDL-c, ALT, AST, AST/ALT, SBP, DBP and MAP decreased and QUICKi and HDL-c increased significantly (p-value for all < 0.05). Also, before and after adjustment based on baseline, the average changes indicated that the levels of insulin, HOMA-IR, TC, TG, LDL-c, SBP, DBP, MAP in the GSE group decreased more than in the control group (p for all < 0.05). Furthermore, the changes in HDL-c were significantly higher in the GSE group (p < 0.05). The between-groups analysis showed a significant decrease in the HOMA-β and AST before and after adjustment based on baseline levels (p < 0.05). Moreover, the changes in QUICKi after adjustment based on baseline levels were higher in the GSE group than in the control group. Also, between-groups analysis showed that the severity of hepatic steatosis was reduced in the intervention group compared to the placebo group (P = 0.002). Conclusions It seems that GSE can be considered one of the appropriate strategies for controlling insulin resistance, hyperlipidemia, hypertension and hepatic steatosis in NAFLD patients. Trial Registration The clinical trial was registered in the Iranian Clinical Trial Registration Center (IRCT20190731044392N1). https://irct.behdasht.gov.ir/trial/61413 . (The registration date: 30/03/2022)